2018
DOI: 10.1002/asia.201800853
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Inverse Pickering Emulsions for Highly Efficient and Recyclable Enzymatic Catalysis

Abstract: Herein, we report the utilization of a submicron Pickering emulsion (SPE) for the encapsulation of enzymes (e.g., lipase from Candida sp.) in water droplets that were solely stabilized by hydrophobic solid or mesoporous silica nanoparticles in toluene for use in biphasic reactions. The catalytic performance of encapsulated lipase was evaluated in the esterification of 1-hexanol and hexanoic acid under stirring-free conditions, which was favorable for maintaining enzymatic activity. Remarkably, the SPE signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…Up to now, there are two kinds of strategies for biphasic enzymatic catalysis in Pickering emulsions. One includes free enzymes located in the inner aqueous phase [12][13][14][15][16][17]. The other includes enzyme-immobilized particles anchored around droplet interfaces [18][19][20][21][22][23][24][25][26], by contrast, it enables enzymes to be recycled, maximizes the contact area between enzymes and substrates, reduces diffusion distance of substrate molecules and improves the stability of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there are two kinds of strategies for biphasic enzymatic catalysis in Pickering emulsions. One includes free enzymes located in the inner aqueous phase [12][13][14][15][16][17]. The other includes enzyme-immobilized particles anchored around droplet interfaces [18][19][20][21][22][23][24][25][26], by contrast, it enables enzymes to be recycled, maximizes the contact area between enzymes and substrates, reduces diffusion distance of substrate molecules and improves the stability of enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al prepared w/o Pickering emulsions stabilized by silica particles of various sizes in the nanometer range to follow the esterification reaction between 1-hexanol and hexanoic acid catalyzed by lipase from Candida sp. 22 As shown in Fig. 2(c) the conversion increased by decreasing the particle size due to a decrease in the average droplet diameter.…”
Section: Introductionmentioning
confidence: 77%
“…In general, examples of PAC are widely found in the field of biocatalysis, where the enzyme (catalyst) is dissolved in the aqueous phase and the solid particles are located at the liquidliquid interface. 15,22,24,47,[54][55][56][57] In most of these examples, silica particles were selected as the emulsifier for the preparation of w/o emulsions to study hydrolysis and esterification reactions using lipase enzymes as the biocatalyst dissolves in water. However, in ref.…”
Section: (A) Pickering Assisted Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…Since MWCNTs are small, the recovery of MWCNT-immobilized enzymes after the reaction is a difficult task. Until now, a series of particles including mesoporous silica [15], polymersomes [16], microgels [17], and carbonaceous microspheres [18] have been used to construct enzyme-containing Pickering emulsions. These reports have confirmed that the immobilization of enzymes using Pickering emulsion systems is a facile and effective means for facilitating the nanoparticle/nanobiocatalyst recovery and reaction product separation.…”
Section: Introductionmentioning
confidence: 99%